(untitled) (Journal of the College of Basic Education, 2026)
This study investigated the effectiveness of a psychological–physical counseling program in enhancing emotional flexibility and performance among junior female athletes participating in air shooting (rifle and pistol). The research was motivated by observed deficiencies in emotional flexibility and performance among this population, particularly under the pressures of competitions and tournaments. Psychological issues such as mood disturbances, tension, anxiety, mild depression, and insomnia were identified, negatively affecting the athletes’ well-being. The lack of attention from coaches and limited engagement with sports psychology specialists further compounded these challenges. A single-group experimental design was employed. The study population included 50 junior female athletes, from which a sample of 24 participants was selected. Two pilot groups of 10 athletes each were used for preliminary trials. Sixteen athletes were excluded due to high baseline emotional flexibility or non-compliance with the counseling program. Based on psychological assessment results, the counseling program was developed according to the athletes’ needs and structured into 14 sessions.Findings revealed statistically significant improvements in both emotional flexibility and performance from pre-test to post-test. These results suggest that the counseling program is effective and may be applied to enhance psychological and performance outcomes across other sports disciplines.